Meningkatkan Hasil Belajar IPS Siswa SD melalui Model Pembelajaran Scramble Pada Materi Keanekaragaman Suku Bangsa dan Budaya - Kori Sundari; Yudi Budianti; Indah Permatasari (Universitas Sarjanawiyata Tamansiswa, 2023)
: Social Studies is one of the subjects taught in primary and secondary schools which has a very important role in helping students think critically, logically, creatively, innovatively, solve problems, have character, and become themselves, noble persons in society. The goal of social learning itself is to make humans good citizens who are aware of the laws and norms in society. This study is a literature study that analyzes and reviews the results of previous subject-specific studies. This type of research uses a literature review approach where the data analysis process places more emphasis on making comparisons between several scientific journals. The results of this study indicate that the application of the Scramble learning model can improve social studies learning outcomes in three aspects, namely cognitive, affective, and psychomotor aspects. The Scramble learning model is a learning model that demands a high concentration of attention from students and improves students' thinking skills. Thus it can be concluded that the Scramble learning model can improve student learning outcomes in the social studies subject of ethnic and cultural diversity.